2018
DOI: 10.1001/jamaoncol.2018.1071
|View full text |Cite
|
Sign up to set email alerts
|

Association of Smoking Status With Recurrence, Metastasis, and Mortality Among Patients With Localized Prostate Cancer Undergoing Prostatectomy or Radiotherapy

Abstract: Current smokers at the time of primary curative treatment for localized prostate cancer are at higher risk of experiencing biochemical recurrence, metastasis, and cancer-specific mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
43
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 46 publications
4
43
0
3
Order By: Relevance
“…Taylor et al 4 reported increased risk of developing lung cancer and higher cardiac mortality in smoking breast cancer patients receiving radiotherapy. Foerster et al 6 found that prostate cancer patients who were current smokers at the time of prostatectomy or beginning radiotherapy had higher risks of locoregional recurrence, developing distant metastases and increased cancer-specific mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taylor et al 4 reported increased risk of developing lung cancer and higher cardiac mortality in smoking breast cancer patients receiving radiotherapy. Foerster et al 6 found that prostate cancer patients who were current smokers at the time of prostatectomy or beginning radiotherapy had higher risks of locoregional recurrence, developing distant metastases and increased cancer-specific mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Tobacco use is recognized as a causative agent for head and neck (H&N) and lung cancers, but not for cancers of the prostate or breast. Still, tobacco use during radiotherapy has been associated with poorer outcomes for all four of these commonly treated malignancies 1 - 6 . Patients with these cancers who continue to smoke during radiotherapy have worse outcomes ranging from increased side effects during treatment to greater late effects including increased mortality from heart disease and second cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Health behaviors (HBs), such as alcohol intake, cigarette consumption, and physical activity, play a major role in disease-free survival among adults with cancer (Carmack, Basen-Engquist, & Gritz, 2011;Chen, Vazquez, Courquin, Donald, & Farwell, 2014;Twiss, Gross, Waltman, Ott, & Lindsey, 2006). More specifically, previous studies found a higher risk of recurrence of prostate, bladder, and breast cancer in daily smokers (Cumberbatch et al, 2018;Foerster et al, 2018). A longitudinal association between a greater alcohol daily consumption and an increased risk of recurrence of breast and bladder cancer has also been shown (Cumberbatch et al, 2018;Simapivapan, Boltong, & Hodge, 2016;Weigl, Hauner, & Hauner, 2018).…”
Section: Introductionmentioning
confidence: 98%
“…Currently, human T-cell leukemia is not only an important cause of cancer-related mortality in third world countries, but among the major factors of death in developed countries. The burden of human T-cell leukemia in developing countries have been increasing not only due to population growth and aging, but also due to the lack of exercise, smoking and unhealthy lifestyle ( Reiner et al, 2019 ; Foerster et al, 2018 ; Nunez et al, 2018 ; Yancik & Ries, 2004 ). Fortunately, a number of treatments, including surgery ( Li et al, 2019 ), radiotherapy ( Mondini et al, 2020 ), chemotherapy ( Almodovar et al, 2019 ), and traditional Chinese medicine therapy ( Hung et al, 2017 ), have been successful to relieve the pain and prolong the life expectancy of patients affected by T-cell leukemia.…”
Section: Introductionmentioning
confidence: 99%